In Vitro Anti-adenovirus Activity and Antioxidant Potential of Pistacia atlantica Desf. Leaves - Ali Karimi; Mohammad-Taghi Moradi*; Asghar Gafourian (Iranian Society of Pharmacognosy, 2020)
Background and objectives: Human adenoviruses cause a wide range of diseases, from self-limiting and mild infections to some life-threatening infections. Many studies have shown that components derived from medicinal plants have antiviral activity. Pistacia genus is rich in phenolic compounds and has antioxidant and antimicrobial effects. The aim of this study was to investigate antioxidant potential and antiviral effects of ethanol and crude extracts and different fractions of Pistacia atlantica Desf. leaves on adenovirus. Methods: Crude P. atlantica leaf extract was prepared by maceration with 80% ethanol. Hexane, chloroform, ethyl acetate and n-butanol fractions were prepared using liquid-liquid extraction method. Toxicity on HEp-2 cells and anti-adenoviral activity of the extract/fractions were evaluated by MTT colorimetric methods. The concentration that caused 50% viral inhibition (IC50) and 50 % cytotoxicity concentration (CC50) were evaluated using regression analysis. Selectivity index (SI), as a marker of antiviral activity, was calculated. To determine antioxidant activity the 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assay was used. Results: Ethyl acetate fraction showed the highest antioxidant activity with IC50of 1.54±0.12 μg/mL in DPPH scavenging assay. Based on our results, IC50 of P. atlantica crude extract on adenovirus was 15.72 μg/mL, with SI of 8.09; n-butanol fraction showed the highest anti-adenoviral activity among the fractions with IC50of 16.38 µg/mL and SI of 26.5. Conclusion: The ethanol extract and n-butanol fraction of P. atlantica leaves showed inhibitory effects on adenovirus and could be a new promising anti-adenovirus agent.